Urban Inequality and Segregation in Europe and China Towards a New Dialogue - Pryce, Gwilym; Wang, Ya Ping; Chen, Yu; Shan, Jingjing; Wei, Houkai (The Urban Book Series,, 2021)
This open access book explores new research directions in social inequality and urban segregation. With the goal of fostering an ongoing dialogue between scholars in Europe and China, it brings together an impressive team of international researchers to shed light on the entwined processes of inequality and segregation, and the implications for urban development. Through a rich collection of empirical studies at the city, regional and national levels, the book explores the impact of migration on cities, the related problems of social and spatial segregation, and the ramifications for policy reform. While the literature on both segregation and inequality has traditionally been dominated by European and North American studies, there is growing interest in these issues in the Chinese context. Economic liberalization, rapid industrial restructuring, the enormous growth of cities, and internal migration, have all reshaped the countryprofoundly. What have we learned from the European and North American experience of segregation and inequality, and what insights can be gleaned to inform the bourgeoning interest in these issues in the Chinese context? How is China different, both in terms of the nature and the consequences of segregation inequality, and what are the implications for future research and policy? Given the continued rise of China's significance in the world, and its recent declaration of war on poverty, this book offers a timely contribution to scholarship, identifying the core insights to be learned from existing research, and providing important guidance on future directions for policy makers and researchers.